Re-organisation of oesophago-gastric cancer care in England: progress and remaining challenges - Greenaway Kimberley; Riley Stuart A; Hardwick Richard H; Cromwell David A; Palser Thomas R; Allum William; van der Meulen Jan HP (BMC, 2009)
Abstract Background Oesophago-gastric cancer services in England have been extensively reorganised since 2001 to deliver a centralised, specialist-led service. Our aim was to assess how well the National Health Service (NHS) in England met organisational standards for oesophago-gastric cancer care. Methods Questionnaires that asked about the provision of staging investigations, curative and palliative treatments and key personnel were sent in September 2007 to the lead clinician for oesophago-gastric cancer at all 30 cancer networks and 156 NHS acute trusts in England. Results Responses were received from all networks and 81% of NHS trusts. All networks provided essential staging investigations and a range of endoscopic palliative therapies. Only 16 of the 30 cancer networks discussed all patients at the specialist multi-disciplinary team meeting and 11 networks had not fully centralised curative surgery. There was also variation between NHS trusts in the integration of the palliative care team, the availability of nurse specialists and the use of dieticians to provide nutritional support. Conclusion There has been considerable progress in reforming oesophago-gastric cancer services but the process of reorganisation is still incomplete and regional differences in service provision exist that may lead to variation in patient outcomes.